Distinct Dengue Disease Epidemiology, Clinical, and Diagnosis Features in Western, Central, and Eastern Regions of Indonesia, 2017–2019 - Sasmono, R. Tedjo; Santoso, Marsha S.; Pamai, Yanuarni W. B.; Yohan, Benediktus; Afida, Anna M.; Denis, Dionisius; Hutagalung, Ingrid A.; Johar, Edison; Hayati, Rahma F.; Yudhaputri, Frilasita A.; Haryanto, Sotianingsih; Stubbs, Samuel C. B.; et al. (Frontiers in Medicine, 2020)
The people of Indonesia has been afflicted by dengue, a mosquito borne viral disease, for over 5 decades. The country is the world’s largest archipelago with diverse geographic, climatic, and demographic conditions that may impact the dynamics of disease transmissions. A dengue epidemiology study was launched by us to compare and understand the dynamic of dengue and other arboviral diseases in three cities representing western, central, and eastern Indonesia, namely Batam, Banjarmasin, and Ambon, respectively. A total of 732 febrile patients were recruited with dengue-like illness during September 2017 – September 2019 and an analysis of their demographic, clinical, and virological features was performed. The seasonal patterns of dengue-like illness were found to be different in the three regions. Among all patients, 271 (37.0%) were virologically-confirmed dengue, while 152 (20.7%) patients were diagnosed with probable dengue, giving a total number of 423 (57.7%) dengue patients. Patients’ age and clinical manifestations also differed between cities. Mostly mild dengue fever was observed in Batam, while more severe cases were prominent in Ambon. While all dengue virus (DENV) serotypes were detected, distinct serotypes dominated in different locations; DENV-1 in Batam and Ambon and DENV-3 in Banjarmasin. We also assessed the diagnostic features in the study sites, which revealed different patterns of diagnostic agreements, particularly in Ambon. To detect the possibility of infection with other arboviruses, further testing on 461 DENV RT-PCR-negative samples was performed using pan-flavivirus and -alphavirus RT-PCRs, however, only one chikungunya infection was detected in Ambon. A diverse dengue epidemiology in western, central and eastern Indonesia was observed which is likely to be influenced by local geographic, climatic, and demographic conditions. Our study adds a new understanding on dengue epidemiology in Indonesia.